Shift from high-frequency to low-frequency episodic migraine in patients treated with Galcanezumab: results from two global randomized clinical trials - Jedynak, Jakub; Eross, Eric; Gendolla, Astrid; Rettiganti, Mallikarjuna; Stauffer, Virginia L. (Journal of headache and pain, 2021)
Background Patients with episodic migraine (EM) with a higher-frequency of migraine headache days (HFEM: 8–14 migraine headache days/month) have a greater disease burden and a higher risk of progressing to chronic migraine (CM) with associated acute treatment overuse versus those with low-frequency EM (LFEM: 4–7 migraine headache days/month). In this post hoc analysis, we assessed the proportions of patients who shifted from HFEM to LFEM and to very low-frequency EM (VLFEM: 0–3 migraine headache days/month) status following treatment with galcanezumab versus placebo. Methods EVOLVE-1 and EVOLVE-2 were double-blind, Phase 3 studies in patients with EM. Patients (18–65 years) were randomized (2:1:1) to subcutaneous monthly injections of placebo, galcanezumab 120 mg (240 mg loading dose) or 240 mg, for up to 6 months. Data were pooled and endpoints were change from baseline in number of migraine headache days/month and patients who shifted from HFEM to LFEM or VLFEM status. Impact of change in HFEM status on migraine headache days/month, quality of life and disability was also assessed. Results A total of 66% (1176/1773) patients from EVOLVE studies had HFEM status at baseline and were included in this analysis; placebo: 592, galcanezumab 120 mg: 294 and galcanezumab 240 mg: 290. At each month, both doses of galcanezumab resulted in a higher proportion of patients who shifted to 0–7 monthly headache days/month (VLFEM or LFEM status). Patients who shifted from HFEM at baseline to VLFEM status at Month 3, a relatively larger proportion of patients on galcanezumab 120 mg versus placebo remained at VLFEM status at Months 4–6; Months 4–5 for galcanezumab 240 mg versus placebo. Among the galcanezumab-treated patients who did-not-shift or shifted to LFEM or VLFEM status for ≥3 consecutive months until the end of the study, patients who shifted from HFEM to VLFEM status experienced the largest reduction in migraine headache days/month and the largest clinically meaningful improvements in daily functioning (MSQ-RFR) and disability (MIDAS). Conclusions In patients with HFEM, treatment with galcanezumab (120 mg and 240 mg) significantly reduced migraine headache days/month, maintained remission status at subsequent months until the end of the study, and improved patients’ quality of life versus placebo. Trial registration ClinicalTrials.gov Identifier: EVOLVE-1, NCT02614183 ; EVOLVE-2, NCT02614196 .